Altered Effective Connectivity in Schizophrenic Patients With Auditory Verbal Hallucinations: A Resting-State fMRI Study With Granger Causality Analysis - Gao, Jie; Zhang, Dongsheng; Wang, Lei; Wang, Wei; Fan, Yajuan; Tang, Min; Zhang, Xin; Lei, Xiaoyan; Wang, Yarong; Yang, Jian; Zhang, Xiaoling (Frontiers in Psychiatry, 2020)
Purpose Auditory verbal hallucinations (AVH) are among the most common and prominent symptoms of schizophrenia. Although abnormal functional connectivity associated with AVH has been reported in multiple regions, the changes in information flow remain unclear. In this study, we aimed to elucidate causal influences related to AVH in key regions of auditory, language, and memory networks, by using Granger causality analysis (GCA). Patients and Methods Eighteen patients with schizophrenia with AVH and eighteen matched patients without AVH who received resting-state fMRI scans were enrolled in the study. The bilateral superior temporal gyrus (STG), Broca’s area, Wernicke’s area, putamen, and hippocampus were selected as regions of interest. Results Granger causality (GC) increased from Broca’s area to the left STG, and decreased from the right homolog of Wernicke’s area to the right homolog of Broca’s area, and from the right STG to the right hippocampus in the AVH group compared with the non-AVH group. Correlation analysis showed that the normalized GC ratios from the left STG to Broca’s area, from the left STG to the right homolog of Broca’s area, and from the right STG to the right homolog of Broca’s area were negatively correlated with severity of AVH, and the normalized GC ratios from Broca’s area to the left hippocampus and from Broca’s area to the right STG were positively correlated with severity of AVH. Conclusion Our findings indicate a causal influence of pivotal regions involving the auditory, language, and memory networks in schizophrenia with AVH, which provide a deeper understanding of the neural mechanisms underlying AVH.